Supramolecular Assembly of Peptide Amphiphiles - Hendricks, Mark P; Sato, Kohei; Palmer, Liam C; Stupp, Samuel I (Accounts of chemical research, 2017)
Peptide amphiphiles (PAs) are small molecules that contain hydrophobic components covalently conjugated to peptides. In this Account, we describe recent advances involving PAs that consist of a short peptide sequence linked to an aliphatic tail. The peptide sequence can be designed to form β-sheets among the amino acids near the alkyl tail, while the residues farthest from the tail are charged to promote solubility and in some cases contain a bioactive sequence. In water, β-sheet formation and hydrophobic collapse of the aliphatic tails induce assembly of the molecules into supramolecular one-dimensional nanostructures, commonly high-aspect-ratio cylindrical or ribbonlike nanofibers. These nanostructures hold significant promise for biomedical functions due to their ability to display a high density of biological signals on their surface for targeting or to activate pathways, as well as for biocompatibility and biodegradable nature. Recent studies have shown that supramolecular systems, such as PAs, often become kinetically trapped in local minima along their self-assembly reaction coordinate, not unlike the pathways associated with protein folding. Furthermore, the assembly pathway can influence the shape, internal structure, and dimension of nanostructures and thereby affect their bioactivity. We discuss methods to map the energy landscape of a PA structure as a function of thermal energy and ionic strength and vary these parameters to convert between kinetically trapped and thermodynamically favorable states. We also demonstrate that the pathway-dependent morphology of the PA assembly can determine biological cell adhesion and survival rates. The dynamics associated with the nanostructures are also critical to their function, and techniques are now available to probe the internal dynamics of these nanostructures. For example, by conjugating radical electron spin labels to PAs, electron paramagnetic resonance spectroscopy can be used to study the rotational diffusion rates within the fiber, showing a liquidlike to solidlike transition through the cross section of the nanofiber. PAs can also be labeled with fluorescent dyes, allowing the use of super-resolution microscopy techniques to study the molecular exchange dynamics between PA fibers. For a weak hydrogen-bonding PA, individual PA molecules or clusters exchange between fibers in time scales as short as minutes. The amount of hydrogen bonding within PAs that dictates the dynamics also plays an important role in biological function. In one case, weak hydrogen bonding within a PA resulted in cell death through disruption of lipid membranes, while in another example reduced hydrogen bonding enhanced growth factor signaling by increasing lipid raft mobility. PAs are a promising platform for designing advanced hybrid materials. We discuss a covalent polymer with a rigid aromatic imine backbone and alkylated peptide side chains that simultaneously polymerizes and interacts with a supramolecular PA structure with identical chemistry to that of the side chains. The covalent polymerization can be "catalyzed" by noncovalent polymerization of supramolecular monomers, taking advantage of the dynamic nature of supramolecular assemblies. These novel hybrid structures have potential in self-repairing materials and as reusable scaffolds for delivery of drugs or other chemicals. Finally, we highlight recent biomedical applications of PAs and related structures, ranging from bone regeneration to decreasing blood loss during internal bleeding.